Implementação de um sistema de monitoramento para redes FTTH utilizando o protocolo LoRaWAN e a aplicação Zabbix - Costa, Ítalo Rossi Araújo (2024)
The internet plays a crucial role in connecting innovative solutions and people, making it essential for Internet Service Providers (ISPs) to offer increasingly secure, reliable, and scalable services. To meet these demands, it is necessary to maintain high availability and quality of the optical networks used to deliver these connections, making network monitoring essential. This research addresses the implementation of a monitoring network based on LoRaWAN technology, focusing on FTTH (Fiber to the Home) optical networks. The goal is to enable real-time data collection for the efficient management of these networks, aiming to reduce repair time and improve signal availability for users. The LoRaWAN protocol is chosen due to its capability to offer long-range communication with low energy consumption, which is ideal for monitoring extensive optical networks. The research details the configuration of the main components of the LoRaWAN network: the network node using the Heltec WiFi LoRa 32 V2 module, the RD43HATGPS gateway, and the ChirpStack network server and Zabbix application server. The Heltec WiFi LoRa 32 V2 was selected for its robustness and energy efficiency, while the RD43HATGPS gateway was chosen for its high power and ability to integrate with the Raspberry Pi 3. The research highlights the efficiency of the implemented system in collecting and managing data from FTTH networks and emphasizes the importance of continuous monitoring of optical networks to ensure service quality and minimize downtime. The use of LoRaWAN technology has proven to be an effective solution for this purpose, providing reliable and low-cost communication.